Harmonising progress: assessing the impact of economic freedom, economic growth, urbanisation and environmental protection expenditures on load capacity in selected European Union countries - Esra Guney; Yasin Sogut; Nazli Demirtas; Yakup Koseoglu; Cahit Sanver (Environmental Sciences Europe)
Abstract This study investigates the relationships between the load capacity factor and urbanization, environmental protection expenditures, economic freedom and economic growth in the European Union from 1996 to 2021. The main motivation is the need for sustainable policies that reduce environmental degradation while promoting economic development. The analysis is conducted with empirical methods such as common correlated effects and augmented mean group using panel data from 24 European Union Countries. The results show that urbanization increases load capacity and can support sustainable practices when well managed. The impact of spending on environmental protection varies across countries, improving environmental quality in some regions but being counterproductive in others. The relationship between economic freedom and growth is complex; economic growth increases environmental pressure, emphasizing the need for green technologies. This highlights the need for sustainable development.. Graphical Abstract